Contact Dermatitis to Thiurams: A Case Report - Lee Chin, Ângela (2018)
Thiurams are used as additives that are added to natural or synthetic latex in the manufacture of rubber products. Hypersensitivity to thiurams is a delayed type IV reaction, mediated by T lymphocytes. The authors present a case of a 9-year-old girl with recurrent episodes of edema and erythema of the eyelids, lips and perioral region, associated with eczema-like lesions, all with previous exposition to rubber materials. Epicutaneous patch test was positive for thiuram mix. With the eviction of these products the girl did not have any more lesions. Many patients referenced for contact dermatitis to rubber products are hypersensitive to rubber additives such as thiurams and carbamates and not to latex.